STRUCTURAL AND CLINICAL FEATURES OF THE ORAL CAVITY IN WOMEN DURING THE POSTMENOPAUSAL PERIOD - Mamedov Izmir; Budaychiev Gasan Magomed-Alievich; Patimat Arsenovna Kurbanova (TADQIQOTLAR, 2026)
ANNOTATION The  relevance  of  this  study  is  determined  by  the  growing  proportion  of postmenopausal women worldwide and the significant impact of hormonal changes on oral health. The decline in estrogen levels after menopause is associated with a wide range  of  alterations  in  the  organs  and  tissues of  the  oral  cavity, including  reduced salivary secretion, mucosal atrophy, decreased bone mineral density, and an increased susceptibility to periodontal diseases and tooth loss. Despite the well-recognized systemic effects of menopause, oral manifestations remain insufficiently studied, particularly from a combined clinical and morphological perspective.  Early  detection  of  structural  and  functional  changes  in  oral  tissues  is essential  for  the  prevention,  timely  diagnosis,  and  effective  management  of  dental diseases in this population. Furthermore,  postmenopausal  women  often  present  with  complex  comorbid conditions, which may exacerbate oral pathologies and complicate treatment strategies. Therefore, a comprehensive clinical and morphological assessment of the oral cavity in this group is of high scientific and practical importance. The findings of this study will contribute to improving diagnostic approaches, optimizing  preventive  measures,  and  developing  personalized  treatment  protocols, ultimately  enhancing  the  quality  of  dental  care  and  overall  quality  of  life  for postmenopausal women.